Safety assessment of the process Renovapet, based on the VACUNITE (EREMA basic and Polymetrix SSP V‐leaN) technology, used to recycle post‐consumer PET into food contact materials - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Andrew Chesson; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP) assessed the safety of the recycling process Renovapet (EU register number RECYC271), which uses the VACUNITE (EREMA basic and Polymetrix SSP V‐leaN) technology. The input consists of hot caustic washed and dried poly(ethylene terephthalate) (PET) flakes mainly originating from collected post‐consumer PET containers, including no more than 5% PET from non‐food consumer applications. The flakes are pre‐decontaminated in a first ■■■■■ reactor at high temperature under vacuum (step 2), then extruded and pelletised. The pellets are crystallised, ■■■■■ and then submitted to solid‐state polycondensation (SSP) in a continuous reactor at ■■■■■ under ■■■■■ and ■■■■■ (step 4). Having examined the challenge test provided, the Panel concluded that step 2 (■■■■■ reactor) and step 4 (■■■■■ and SSP) are critical for determining the decontamination efficiency of the process. The operating parameters to control the performance are temperature, pressure and residence time for steps 2 and 4 as well as gas velocity for step 4. It was demonstrated that this recycling process is able to ensure that the level of migration of potential unknown contaminants into food is below the conservatively modelled migration of 0.1 μg/kg food. Therefore, the Panel concluded that the recycled PET obtained from this process is not of safety concern, when used at up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs, including drinking water, for long‐term storage at room temperature, with or without hotfill. Articles made of this recycled PET are not intended to be used in microwave and conventional ovens and such uses are not covered by this evaluation.